Hydrological simulation and prediction of soil erosion using the SWAT model in a mountainous watershed: a case study of Murat River Basin, Turkey - Karakoyun, Erkan; Kaya, Nihat (Iwa Publishing, 2022)
The Euphrates-Tigris basin in Turkey suffers from sedimentation and erosion problems. The purpose of this study was to estimate streamflow, sediment yield, and identification of soil erosion-prone areas for the Murat River Basin which is the headwater of Euphrates River, with Soil and Water Assessment Tool (SWAT). The model was calibrated and validated with observed streamflow and sediment yield data obtained from two gauging stations. The statistical model performance was evaluated by using NSE, R2, and PBIAS. NSE values were calculated as0.57, 0.50 and 0.77, 0.75 for the stations E21A074 and E21A077, respectively, in the monthly streamflow calibration and validation periods. Monthly sediment yield generated the NSE values for stations E21A074 and E21A077 were 0.54, 0.69 and 0.62, 0.35 in the calibration and validation periods, respectively. Spatial analysis indicates that 3.9% of the basin is under very severe (.20 t/ha/y), and 21.3% is under severe(.10 t/ha/y) soil erosion conditions. Most of the soil erosion occurs at the barren land use and in the sub-watersheds with a slope greater than 25%. Overall, the SWAT model satisfactorily simulated the streamflow and sediment yield, and identified the erosion-prone areas at the sub-watershed scale at the Murat River Basin for water resource management.
Keywords: Euphrates-Tigris basin; sediment yield; soil erosion; streamflow; SWAT model; watershed management; Sediment Yield; Rusle Model; Flow; Uncertainty; Quality; Calibration; Streamflow; Transport; Runoff; Europe